Diagnóstico, tratamento e prevenção da osteonecrose maxilar relacionada a medicamentos (Revista Brasileira Multidisciplinar, 2021)
Medication-related osteonecrosis of the jaws (MRONJ) is a rare and serious adverse effect of anti-resorptive and/or antiangiogenic therapy that can cause necrotic bone exposure in the oral cavity, which affects patients’ quality of life. The present study aimed to review literature regarding MRONJ with special focus on diagnostic and treatment. The databases PubMed, Scielo and Google Scholar were searched for reports regarding diagnostic and treatment of MRONJ. Even though this disorder shows poor response to treatment, there is an increase in cure rates when early diagnosed and treated. In this way, systematic dental follow-up of patients under anti-resorptive and/or antiangiogenic therapy is essential for the identification of signs and symptoms suggestive of MRONJ like pain, swelling or dental mobility. Radiographic and tomographic features like increase of bone density, bone sclerosis or osteolysis, persisting alveolar socket, periosteal neoformation, lamina dura widening and mandibular canal widening may indicate bone necrosis. Since there is no universally accepted treatment to cure MRONJ, the management involves symptom palliation and control of associated infection, and surgical excision of necrotic bone is recommended for more severe cases. Each case must be individually evaluated by a multidisciplinary team, allowing dental and medical discussion. The prevention of MRONJ by patients education, elimination of risk factors and oral health maintenance is still the most important measure in the management of these patients.
Keywords: osteonecrosis; clinical clerkship; primary prevention; dental radiography; infections